PELATIHAN MICROSOFT OFFICE DALAM MEDUKUNG HARD SKILL REMAJA MASJID AL-HIKMAH PERUM TAMAN HANG TUAH LEGENDA MALAKA BATAM CENTER - Amrizal Amrizal; Rika Harman; Sasa Ani Arnomo (PUAN INDONESIA, 2023)
The implementation of community service activities carried out in the form of training on the use of Microsoft Word is very useful for young people of the Al-Hikmah Mosque Housing Taman Hangtuah Legenda Malaka Batam Center, because with this ability it will make it easier for Youth of the Al-Hikmah Mosque Housing Taman Hangtuah Legenda Malaka Batam Center in management and operational of the Youth Secretariat of Al-Hikmah Mosque Housing Taman Hangtuah Legenda Malaka Batam Center in its creative activities which are not only spiritual in nature, but also other social activities that support hard skill abilities which are not only obtained in the school environment but can also be obtained in the residential environment in the form of Youth organization Al-Hikmah Mosque Housing Taman Hangtuah Legenda Malaka Batam Center. community service activities by applying the method of making activity reports, correspondence and correspondence as well as making information technology-based outreach brochures by utilizing existing applications in Microsoft Word with the hope that this activity will be able to provide creativity, optimize existing IT facilities and increase capabilities and human resources especially for the young person of the Al-Hikmah Mosque, Taman Hangtuah Residential, the Legenda Malaka, Batam Center. For this activity wil make a good shoft skil to the youth of the Al-hikmah mosque